2022
DOI: 10.5194/acp-22-14059-2022
|View full text |Cite
|
Sign up to set email alerts
|

Inverse modelling of Chinese NOx emissions using deep learning: integrating in situ observations with a satellite-based chemical reanalysis

Abstract: Abstract. Nitrogen dioxide (NO2) column density measurements from satellites have been widely used in constraining emissions of nitrogen oxides (NOx = NO + NO2). However, the utility of these measurements is impacted by reduced observational coverage due to cloud cover and their reduced sensitivity toward the surface. Combining the information from satellites with surface observations of NO2 will provide greater constraints on emission estimates of NOx. We have developed a deep-learning (DL) model to integrate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Process-based modeling studies to identify inconsistencies in NEI emission estimates (and trends) relative to observed pollutant levels must be pursued. The use of CTMs for multi-pollutant emission estimation and data assimilation studies, e.g., refs , together with the application of source apportionment and attribution strategies, e.g., refs , including machine-learning approaches, , provide opportunities to reduce uncertainties in these emission estimates. This should, however, be conducted in association with improvements in input and ancillary datasets that account for local heterogeneity especially land cover classification and urban development, e.g., refs and , as well as emission trends and scenarios like changes in mobile and stationary sources, e.g., ref , and even the shift to renewable energy, , increasing contribution of noncombustion sources, , all of which can drive potential shifts in chemical regimes.…”
Section: Steps Forwardmentioning
confidence: 99%
“…Process-based modeling studies to identify inconsistencies in NEI emission estimates (and trends) relative to observed pollutant levels must be pursued. The use of CTMs for multi-pollutant emission estimation and data assimilation studies, e.g., refs , together with the application of source apportionment and attribution strategies, e.g., refs , including machine-learning approaches, , provide opportunities to reduce uncertainties in these emission estimates. This should, however, be conducted in association with improvements in input and ancillary datasets that account for local heterogeneity especially land cover classification and urban development, e.g., refs and , as well as emission trends and scenarios like changes in mobile and stationary sources, e.g., ref , and even the shift to renewable energy, , increasing contribution of noncombustion sources, , all of which can drive potential shifts in chemical regimes.…”
Section: Steps Forwardmentioning
confidence: 99%
“…However, the lack of real-time economic statistics makes it challenging to timely monitor the economic recovery . Previous studies have disclosed that ambient nitrogen dioxides (NO 2 ), a reactive and short-lived gas mainly released from fuel combustion, , respond to emergency actions swiftly and fluctuate dynamically with the changes in anthropogenic activities and emissions, particularly during and after the COVID-19 lockdowns. The sensitivity of NO 2 concentrations to socioeconomic changes has been witnessed on a global scale. , NO 2 tropospheric vertical column densities (TVCDs) retrieved from satellite observations have played an important role in monitoring ambient NO 2 concentrations, economic activities, and anthropogenic emission variations. Here we investigate the daily dynamics of satellite-observed NO 2 around the Chinese New Year (CNY) in China since 2005. Chemical transport models, high-resolution emission inventories, and population density distribution maps are utilized to attribute the NO 2 changes to emission sectors and regions, which helps us to understand the drivers of satellite-observed NO 2 changes.…”
Section: Introductionmentioning
confidence: 99%
“…The data‐driven approach provides an efficient way of integrating multisource data and predicting atmospheric compositions, which could be used as a useful supplement to process‐driven chemical transport models (CTMs). Recent studies demonstrated applications of data‐driven techniques to provide air quality forecasts (Bi et al., 2022; Zhang et al., 2023), spatial extensions of atmospheric observations (Liu et al., 2022; Wei et al., 2023), more accurate or rapid CTM simulations (Shen et al., 2022; Xing et al., 2020), and atmospheric pollutant emission estimates (He et al., 2022b; Xing et al., 2022). Furthermore, recent studies have highlighted the importance of data‐driven techniques to provide a better understanding of atmospheric ozone (O 3 ), for example, the contributions of meteorological and anthropogenic sources to observed O 3 changes (Chen et al., 2023; Wang et al., 2023; Weng et al., 2022).…”
Section: Introductionmentioning
confidence: 99%